Fatigue-caused damage in trabecular bone from clinical, morphological and mechanical perspectives. (April 2020) - Mirzaali, M.J.; Libonati, F.; Böhm, C.; Rinaudo, L.; Cesana, B.M.; Ulivieri, F.M.; Vergani, L.
Highlights: Experimental fatigue tests on ex-vivo porcine trabecular bone samples are performed. Fatigue-induced damage on bone microarchitecture is studied by means of μCT imaging. A new fatigue model based on specimen-specific effective area is proposed. Abstract: Bone quantity and quality are considered the main predictors of bone mechanical properties ( i.e., strength and fracture resistance). These factors deal with the morphology and chemical composition of bone and can be assessed by non-invasive techniques such as dual-energy x-ray absorptiometry (DXA), providing the bone mineral density (BMD) and the trabecular bone score (TBS). These parameters, and in particular BMD, are currently used as clinical predictors of fracture risk but do not provide information regarding the fatigue life. Bone is continuously subjected to fatigue loading and fatigue-induced damage can be crucial in fragility fractures. To probe the effect of fatigue-induced damage on bone microarchitecture and elucidate the effect of such damage on the bone clinical parameters, we combined fatigue testing on ex-vivo porcine trabecular bone samples with DXA measurements and μCT imaging. In addition, we performed interrupted cyclic tests at different load levels and measured fatigue-induced damage accumulation in the form of stiffness degradation. We also highlighted the change of clinical and microstructural parameters during the accumulation of fatigue-induced damage in interrupted fatigue tests. Our results suggest that the parameters obtained from the current non-invasive diagnostic protocols ( i.e. μCT and DXA) are not able to assess the amount of fatigue-induced damage. This can be due to the fact that such techniques provide global parameters, whereas fatigue-induced damage is a local phenomenon, closely connected to the microarchitecture.